2009
DOI: 10.1590/s1984-46702009000200016
|View full text |Cite
|
Sign up to set email alerts
|

Ecology of ticks in a taxocenosis of snakes from the Serra do Mendanha, Rio de Janeiro, Brazil, with new host records

Abstract: We studied the ecology of ticks found in different species of a taxocenosis of snakes from the Serra do Mendanha, an area of Atlantic Rainforest located in the state of Rio de Janeiro, southeastern Brazil. Snakes were sampled monthly in the field during a period of 48 months. The specific identity of the hosts and their parasites, the number of parasites, and and snout-vent length and body mass of each host were recorded. A total of 25% of the species of snakes in the area were parasitized by ticks (larvae, ny… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0
22

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(36 citation statements)
references
References 23 publications
1
13
0
22
Order By: Relevance
“…These results may have been influenced by the fact that snakes captured in the field sometimes spend several weeks in regional serpentaria and only later are sent to the Institute Vital Brazil, by which time ticks may have detached. However, the rare field studies that exist report that only a few individual snakes are parasitized by ticks in nature (Pontes et al ., ; Viana et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…These results may have been influenced by the fact that snakes captured in the field sometimes spend several weeks in regional serpentaria and only later are sent to the Institute Vital Brazil, by which time ticks may have detached. However, the rare field studies that exist report that only a few individual snakes are parasitized by ticks in nature (Pontes et al ., ; Viana et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Amblyomma rotundatum Koch is a parthenogenetic tick (ARAGÃO, 1912;OBA;SCHUMAKER, 1983) commonly associated with species of reptiles and amphibians (DURDEN;KNAPP, 2005;PONTES et al, 2009;GUGLIELMONE;NAVA, 2010). Experimental studies have shown that during its life cycle, this species uses two or three different host species (OBA;SCHUMAKER, 1983;RODRIGUES et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In Brazil, except for the broad study by Pontes et al (2009) involving ticks associated with a community of snakes in the Atlantic Forest, most studies have been limited to recording parasitism of reptiles by ticks in random samples, usually restricted to a few individual specimens (LABRUNA et al, 2002(LABRUNA et al, , 2005DANTAS-TORRES et al, 2005MARTINS et al, 2007;LOPES et al, 2010), studies involving captive hosts (see review in GUGLIELMONE; NAVA, 2010), or characterization of the life cycle of ticks Amblyomma dissimile or A. rotundatum under experimental conditions (ARAGÃO, 1912;OBA;SCHUMAKER 1983;FREITAS et al, 2004;RODRIGUES et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…This tick has been reported to be a parasite of A. ameiva (ONOFRIO, 2007), but data about the location were not reported. According to Pontes et al (2009), data on A. dissimile The lizard A. ameiva inhabits a range of ecosystems and is abundant in natural and anthropogenic areas (VITT; COLLI, 1994). Thus, it represents a potential host for ticks of the genus Amblyomma.…”
Section: Introductionmentioning
confidence: 99%
“…This tick has been reported to be a parasite of A. ameiva (ONOFRIO, 2007), but data about the location were not reported. According to Pontes et al (2009), data on A. dissimile ISSN 0103-846X (impresso) / ISSN 1984-2961 Review Article Research Note v. 19, n. 4, out.-dez. 2010 A first record of Amblyomma Dissimile (Acari: Ixodidae) parasitizing the lizard Ameiva Ameiva (Teiidae) in Brazil 263…”
mentioning
confidence: 99%